Good Recordkeeping Staff are Hard to Find Down Under! - Pember, Margaret (RMAA, 2006)
There is a serious lack of qualified recordkeeping professionals in Australia. Despite advertising and readvertising, RM positions are sometimes difficult to fill and remain vacant for long periods. What are the solutions?Good recordkeeping staff are difficult to recruit and keep in Western Australia. They are in very short supply. In a 2004 survey of recordkeeping in the State Public Sector 52.3% of employers admitted that current records management sections did not possess the necessary skills to implement the requirements of the State Records Act 2000. Research by Evans (2002, 2003) indicates that this problem is not limited to Western Australia.Recordkeeping positions are often vacant for significant periods of time, and sometimes appointments are made that are less than satisfactory. Employers who do not value and nuture staff will find the best will be enticed into better paid, more satisfying positions in other organisations. The career prospect for competent professional recordkeeping staff is vibrant indeed.